Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/0095798421997217
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Trauma Symptoms Among Nonpartner Sexual Violence Victims and Nonvictims in Urban Haiti’s Cité Soleil Neighborhood

Abstract: Women in resource-constrained, postdisaster, urban enclaves, such as Haiti’s Cité Soleil, are at risk for nonpartner sexual violence (NPSV) by multiple perpetrators, and subsequently, psychological trauma and sexually transmitted infections (STIs), including HIV/AIDS. These biopsychosocial risks suggest that NPSV victims may benefit from an adapted evidence-based intervention for sexually transmitted infection (EBI-STI) that includes a trauma component. Yet there is a dearth of knowledge on trauma symptoms exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…[7-8] Victims in previous studies also reported shame and discomfort experienced in health care settings among reasons that they did not seek post-NPSV care, so that even if those settings could provide PeP, they were not accessing it. [7-8; 11]…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[7-8] Victims in previous studies also reported shame and discomfort experienced in health care settings among reasons that they did not seek post-NPSV care, so that even if those settings could provide PeP, they were not accessing it. [7-8; 11]…”
Section: Introductionmentioning
confidence: 99%
“…[11] Kadejak involves multiple aggressors, deliberate reproductive injuries, psychological trauma, and heightened risks of sexually transmitted infections (STIs). [7][8][9][10][11] Addressing the HIV susceptibility of women who survive NPSV in that context must take into account the characteristics of the NPSV, that their HIV risk profile involves sexual risk behaviors that are forced and beyond their control, and that they have little awareness of the risks associated with kadejak experiences. [3; 11-13] Evidence-based interventions for HIV (EBI HIV) can increase these women's HIV awareness, lead to HIV testing, and reduce HIV risk.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations